Association of serum mannose-binding lectin, anti-phospholipase A2 receptor antibody and renal outcomes in idiopathic membranous nephropathy and atypical membranous nephropathy: a single center retrospective cohort study. Issue 1 (31st December 2022) - Zhao, Yuchao; Cai, Meishun; Jiang, Zhenbin; Dong, Bao; Yan, Yu; Wang, Yina; Zuo, Li
Abstract: Objectives: Idiopathic membranous nephropathy (iMN) is a major cause of nephrotic syndrome. Atypical membranous nephropathy (aMN) is a new type of nephropathy in China, characterized by a 'full-house' on immunofluorescent examination, that is IgG, IgA, IgM, C3, C1q positive, but without clinical evidence of a secondary cause. Phospholipase A2 receptor (PLA2R) was the major target antigens in iMN patients. Activation of the mannose-binding lectin (MBL) pathway plays a vital role in the development of MN. Our objective was to investigate the role of PLA2R and MBL in the pathogenesis of iMN and aMN. Methods: We conducted a retrospective observational study using propensity score matching by age, gender, and eGFR. All clinical, laboratory data, and follow-up data of the patients were collected. Serum levels of anti-PLA2R antibodies and MBL were tested. Results: Finally, 30 iMN patients and 30 aMN patients were included, and 20 healthy controls were retrospectively collected in this study. The 24 h proteinuria level was higher and serum albumin was lower in anti-PLA2R (+) patients than in anti-PLA2R (−) patients in both iMN and aMN groups. In aMN patients, MBL levels were significantly higher in anti-PLA2R (+) patients than in anti-PLA2R (−) patients ( p = .045). The serum level of anti-PLA2R positively correlated with no-remission in both iMN and aMN groups. Conclusions: The complement lectin pathway has an association with the development of MN, especially in patients with positive anti-PLA2R antibodies. Serum MBL cannot differentiate between the two diseases. Serum MBL levels are not associated with clinical manifestations, nor with prognosis.